Unsur Pembangun Naskah Drama Sudah Gila Karya Chairil Anwar - Iktarna Faris Saufaqillah; Akhmad Fatoni (STIKes Ibnu Sina Ajibarang, 2025)
This study aims to analyze the structure of the drama script by Chairil Anwar entitled